Strong dependence of air stability on thickness in n-doped carbon nanotube thermoelectrics - Dörling, Bernhard; Hawkey, Angus; Zaumseil, Jana; Campoy-Quiles, Mariano (Applied physics letters, 2024)
We demonstrate that the observed (in-)stability of n-doped carbon nanotube films in air not only depends on the employed dopant but is also strongly affected by sample-specific factors, such as the film thickness and density. We show this for two typical dopants, polyethylenimine and a potassium crown ether complex, by preparing films of increasing thickness. We argue that reports on dopant stability cannot be properly assessed without knowledge of these sample-specific parameters, which explains some of the conflicting results in the literature.
Online veröffentlicht: 14. März 2024
Gesehen am 14.08.2024